Diagnosis of Aspergillosis in Horses - Dobiáš, Radim; Jahn, Petr; Tóthová, Katarina; Dobešová, Olga; Višňovská, Denisa; Patil, Rutuja; Škríba, Anton; Jaworská, Pavla; Škorič, Miša; Podojil, Libor; Kantorová, Michaela; Mrázek, Jakub; et al. (Journal of fungi (Basel, Switzerland), 2023)
Invasive pulmonary aspergillosis (IPA) may be a rare cause of granulomatous pneumonia in horses. The mortality of IPA is almost 100%; direct diagnostic tools in horses are needed. Bronchoalveolar lavage fluid (BALF) and serum samples were collected from 18 horses, including individuals suffering from IPA (n = 1), equine asthma (EA, n = 12), and 5 healthy controls. Serum samples were collected from another 6 healthy controls. Samples of BALF (n = 18) were analyzed for Aspergillus spp. DNA, fungal galactomannan (GM), ferricrocin (Fc), triacetylfusarinin C (TafC), and gliotoxin (Gtx). Analysis of 24 serum samples for (1,3)-β-D-glucan (BDG) and GM was performed. Median serum BDG levels were 131 pg/mL in controls and 1142 pg/mL in IPA. Similar trends were observed in BALF samples for GM (Area under the Curve (AUC) = 0.941) and DNA (AUC = 0.941). The fungal secondary metabolite Gtx was detected in IPA BALF and lung tissue samples (86 ng/mL and 2.17 ng/mg, AUC = 1).
Keywords: fungal secondary metabolites; tracheal wash; galactomannan; bronchoalveolar lavage fluid; serum; guttural pouch; equine herpes virus-5; equine aspergillosis; (1,3)-β-D-glucan; equine asthma; invasive pulmonary aspergillosis